Peran Permainan Tradisional terhadap Karakter Kepemimpinan Anak Usia 10-12 Tahun - Chrismantari, Linda; Nugrahanta, Gregorius Ari (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
The research aimed to develop a traditional game-based leadership character education manual for 10-12 year olds. This research involved 10 teachers from various regions, 10 validators, and 8 children aged 10-12 years. The results of the study showed that 1) the character education handbook was developed using the ADDIE stages; 2) The quality of the manual showed a score of 3.90 (scale 1-4) in the category "Very good" and "no need for revision"; 3) The guidebook had an effect on the character of leadership. The mean score at the end (M = 3.7625, SE = 0.6797) was higher than the mean score at the beginning (M = 2.0500, SE = 0.8660). Significance test t (7) = 14.616; p < 0.05. The level of influence in the "big effect" category, namely r = 0.98, meant that the guidebook could explain 96.83% of the variance changes in leadership character. The effectiveness level of the N-gain score was in the "High" category or 87.82%.